Hubungan Depresi dan Dukungan Keluarga terhadap Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe 2 Di RSUD Sragen - Isworo, Atyanti; Saryono (Jurusan Keperawatan FIKES UNSOED, 2010)
Diabetes Mellitus (DM) is a chronic metabolic disease that may have debilitating effect toward the whole life of type 2 diabetic patient, not only the physical aspect but also psychological aspect. Depression is one psychological disorder, therefore this condition requires a comprehensive management with involving family on nursing care. The purpose of this study was to identify the correlation among depression and family support with blood glucose level of type 2 DM patients. This study used an analytic correlational design with cross-sectional approach, recruited 166 respondents by purposive sampling method at Outpatient Ward of Internal Medicine Clinic, Sragen Public Hospital on September until November 2008. The CES-D (Center for Epidemiological Studies-Depressed Mood Scale) was used to assesed depressive symptoms while the DFBC (The Diabetes Family Behavior Checklist) to determine the total score of family support. Chi Square, t-test independent and a multiple logistic regression were used to examine the relationship of depression and family support with blood glucose. The result revealed that there were significant relationships among depression and blood glucose level (p value 0,0005) and family support (p=0,0005). There was no significant correlation between economic status and blood glucose level (p=0,052). In addition, family support became the most dominant factor related to blood glucose level (OR=10,925). Meanwhile, age, education level, and complications became the confounding factors. It concluded that there were relationship among depression and family support with blood glucose level of type 2 DM patients. The findings of this study suggested that screening individuals with diabetes for depressive symptoms and participation of family would be important aspect of diabetes care.